School choice tradeoffs : liberty, equity, and diversity - Godwin, R. Kenneth (University of Texas Press, 2002)
Educational policy in a democracy goes beyond teaching literacy and numeracy. It also supports teaching moral reasoning, political tolerance, respect for diversity, and citizenship. Education policy should encourage liberty and equality of opportunity, hold educational institutions accountable, and be efficient. School choice tradeoffs examines the tradeoffs among these goals when government affords parents the means to select the schools their children attend. Godwin and Kemerer compare current policy that uses family residence to assign students to schools with alternative policies that range from expanding public choice options to school vouchers. They identify the benefits and costs of each policy approach through a review of past empirical literature, the presentation of new empirical work, and legal and philosophic analysis. The authors offer a balanced perspective that goes beyond rhetoric and ideology to offer policymakers and the public insight into the complex tradeoffs that are inherent in the design and implementation of school choice policies.